The Effect of Green Accounting Disclosure, CSR and Financial Performance on Company Value: PT Vale Indonesia - Mallo, Lisa Puspa Dewi; Riyanti, Riyanti; Syamsuddin, Sofyan (PT. EQUATOR SINAR AKADEMIA, 2026)
Mining companies have a very close relationship with their surrounding environment. The way companies treat the environment needs to be seriously considered. In addition to the environment, they are also required to consider social aspects. This study examines the effect of green accounting and CSR disclosure on company value at PT Vale Indonesia for the period 2015-2024, with financial performance as a moderating variable. The research method used was a descriptive quantitative approach analysed with panel data regression via EViews 13, including t-tests, F-tests, and determination coefficients; variables were measured using the BL formula for X1, CSRI for X2, Tobin's Q for Y, and ROA for Z. The results show that CSR has a significant positive effect on company value, while green accounting is not significant, and financial performance moderation is not significant for both. The simultaneous effect is not significant. With these implications, mining companies are advised to prioritise CSR to increase market value via positive investor signals; green accounting needs to be better integrated with financial strategies; IDX regulators should encourage quality sustainable disclosure to reduce information asymmetry.